Story of Australian Wheat - Nunn, Frank (Indian Forester, 1946)
"India hopes to receive during this month alone 50,000 tons of Australian wheats"-Report of statement by Sir J. P. Srivastava, Food Member, at a Press Conference in Lahore during January. On the wheatgrowers of Australia has fallen much of the task of feeding a hungrY world. Large quantities of Australian wheat were supplied to India and to other countries last year. This is the story of the Australian wheat industry.